2000
DOI: 10.1038/35048617
|View full text |Cite
|
Sign up to set email alerts
|

Metal-ion coordination by U6 small nuclear RNA contributes to catalysis in the spliceosome

Abstract: Introns are removed from nuclear messenger RNA precursors through two sequential phospho-transesterification reactions in a dynamic RNA-protein complex called the spliceosome. But whether splicing is catalysed by small nuclear RNAs in the spliceosome is unresolved. As the spliceosome is a metalloenzyme, it is important to determine whether snRNAs coordinate catalytic metals. Here we show that yeast U6 snRNA coordinates a metal ion that is required for the catalytic activity of the spliceosome. With Mg2+, U6 sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
209
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(228 citation statements)
references
References 26 publications
(41 reference statements)
12
209
1
1
Order By: Relevance
“…In spite of the high conservation of the structure of this element and the apparent conservation of its function as shown by these studies, we do not have a clear idea of what its function might be in the spliceosome+ Its location near the sites of splicing chemistry have led to speculation that it plays a role in the active site of the spliceosome (reviewed in Nilsen, 1998;Collins & Guthrie, 2000)+ Several groups have suggested parallels with features of various ribozymes including the hairpin ribozyme (Tani & Ohshima, 1991;Sun & Manley, 1995) and domain 5 of group II self-splicing introns (see discussions in Sun & Manley, 1997;Costa et al+, 1998;Nilsen, 1998)+ The group II domain 5 comparison is particularly interesting+ A recent revision of the proposed structure of the domain 5 stem-loop has emphasized the similarity between it and the U6 (or U6atac) intramolecular stem-loop (Costa et al+, 1998)+ A phosphorothioate modification-interference study of domain 5 in self-splicing identified a phosphate group in the bulge region as important for splicing catalysis (Chanfreau & Jacquier, 1994)+ This phosphate is located in a very similar position to one identified as important for U6 snRNA function in in vitro pre-mRNA splicing in both yeast (Fabrizio & Abelson, 1992) and nematodes (Yu et al+, 1995)+ Recent investigations of both phosphorothioate diastereomers at this position in yeast U6 snRNA have revealed a metal ion specificity switch for the first step of splicing (Yean et al+, 2000)+ This suggests that U6 snRNA participates in the catalysis of splicing through metal ion coordination and places this stem-loop element at or very near the catalytic center of the spliceosome+ Pyle's group has also suggested that the bulge and lower stem regions of domain 5 serve to position a critical metal ion for group II splicing (Konforti et al+, 1998)+ Such a function would mainly involve the positioning of phosphate groups to coordinate the metal and would be compatible with many but perhaps not all base paired sequences within the stem region+ Basespecific interactions would be limited to residues in unpaired regions and functional groups in the major and minor groves of the helical regions+ Such a function would fit with the apparent tolerance of the stem regions of U6atac snRNA for many but not all substitutions that maintain base pairing+…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the high conservation of the structure of this element and the apparent conservation of its function as shown by these studies, we do not have a clear idea of what its function might be in the spliceosome+ Its location near the sites of splicing chemistry have led to speculation that it plays a role in the active site of the spliceosome (reviewed in Nilsen, 1998;Collins & Guthrie, 2000)+ Several groups have suggested parallels with features of various ribozymes including the hairpin ribozyme (Tani & Ohshima, 1991;Sun & Manley, 1995) and domain 5 of group II self-splicing introns (see discussions in Sun & Manley, 1997;Costa et al+, 1998;Nilsen, 1998)+ The group II domain 5 comparison is particularly interesting+ A recent revision of the proposed structure of the domain 5 stem-loop has emphasized the similarity between it and the U6 (or U6atac) intramolecular stem-loop (Costa et al+, 1998)+ A phosphorothioate modification-interference study of domain 5 in self-splicing identified a phosphate group in the bulge region as important for splicing catalysis (Chanfreau & Jacquier, 1994)+ This phosphate is located in a very similar position to one identified as important for U6 snRNA function in in vitro pre-mRNA splicing in both yeast (Fabrizio & Abelson, 1992) and nematodes (Yu et al+, 1995)+ Recent investigations of both phosphorothioate diastereomers at this position in yeast U6 snRNA have revealed a metal ion specificity switch for the first step of splicing (Yean et al+, 2000)+ This suggests that U6 snRNA participates in the catalysis of splicing through metal ion coordination and places this stem-loop element at or very near the catalytic center of the spliceosome+ Pyle's group has also suggested that the bulge and lower stem regions of domain 5 serve to position a critical metal ion for group II splicing (Konforti et al+, 1998)+ Such a function would mainly involve the positioning of phosphate groups to coordinate the metal and would be compatible with many but perhaps not all base paired sequences within the stem region+ Basespecific interactions would be limited to residues in unpaired regions and functional groups in the major and minor groves of the helical regions+ Such a function would fit with the apparent tolerance of the stem regions of U6atac snRNA for many but not all substitutions that maintain base pairing+…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of RNA-RNA interactions in U2-and U12-dependent spliceosomal splicing+ A: Diagram of the interactions between the pre-mRNA and U1, U2, and U6 snRNAs+ Shown are the U2-branch site interaction, the U1 and U6-59 splice site interactions and the Helix Ia and Ib interactions between U2 and U6 snRNAs+ Also shown is the U6 intramolecular stem-loop structure that immediately follows Helix Ib+ B: Diagram of the analogous interactions between the pre-mRNA and U11, U12, and U6atac snRNAs+ Shown are the U12-branch site interaction, the U11 and U6atac-59 splice site interactions and the U12-U6atac interactions and the U6atac stem-loop structure+ Also shown in the shaded boxes are the mutations used in the in vivo mutational suppression assay+ The P120 CC5/6GG mutation shown in the middle of the upper box inactivates U12-dependent splicing+ The U6atac GG14/15CC mutation restores splicing at the mutant 59 splice site and the U11 GG6/7CC mutation enhances the level of suppression+ functionally active snRNA when tested in vivo (Shukla & Padgett, 1999)+ In addition to the indirect evidence of the importance of the U6 snRNA intramolecular stem-loop provided by phylogenetic conservation, experimental support has also been provided by several studies+ Genetic suppression experiments in yeast have shown that formation of the stem-loop structure is required for splicing (Fortner et al+, 1994;McPheeters, 1996)+ Similar experiments in mammalian systems also showed a requirement for this structure (Wolff & Bindereif, 1993;Sun & Manley, 1995+ In an extensive set of experiments, Sun and Manley (1997) used an in vivo approach to show that U6 snRNA function was maintained as long as the base pairing pattern and a critical U residue in the bulge were conserved+ Other structural modifications were also compatible with function including pairing of the bulged U residue and extension of the helix by an additional base pair+ These results are quite surprising in light of the very high conservation of this region over more than a billion years of evolution+ Results from in vitro modification studies of residues within the U6 intramolecular stem-loop provide additional support for its role in splicing+ In both yeast (Fabrizio & Abelson, 1992) and nematode (Yu et al+, 1995) in vitro splicing systems, phosphorothioate modification of certain phosphodiester bonds blocks splicing+ Such a block could be due to disruption of either RNAprotein interactions or interactions with functional chemical groups such as metal ions required for catalysis or the maintenance of a catalytically active structure (Eckstein, 1985)+ A recent analysis of one of these positions in yeast U6 snRNA has identified a critical metal-ion binding site in the bulge region (Yean et al+, 2000)+ These and other results have led to speculation that this element of U6 snRNA functions at or near the catalytic center of the spliceosome (reviewed in Nilsen, 1998;Collins & Guthrie, 2000)+ Because our earlier experience with substituting the plant U6atac snRNA stem-loop into human U6atac suggested that there was significant sequence flexibility ...…”
Section: Introductionmentioning
confidence: 99%
“…The engagement of U5 loop 1 with the 59 exon would most likely occur when the conserved 59 splice site GU is identified+ Identification of the 59 splice site is thought to take place in steps with sequential inspection of this splicing signal+ To date, a number of factors have been implicated in 59 splice site selection+ Initial recognition of the 59 splice site is through binding of the U1 snRNP and associated proteins to the 59 splice site (Reed, 2000)+ Interactions of the U1 snRNA with the U5 snRNA in mammalian cells (Ast & Weiner, 1997) and the yeast U1 snRNP protein Prp40 with Prp8 (Abovich & Rosbash, 1997) suggest an early interaction between these snRNPs+ These interactions may take place before U5 loop 1 nt U96 to U99 are positioned at the 59 splice site+ Prior to activation of the spliceosome it appears that the U6 snRNA and Prp8 may play important roles in identifying the GU at the 59 splice site+ Mutations in U6 can compensate for mutations in the G residue suggesting a role of U6 in recognition of this nucleotide during splicing (Kandels-Lewis & Séraphin, 1993;Lesser & Guthrie, 1993)+ In addition, a direct interaction between U6 and the invariant GU has been shown by crosslinking (Kim & Abelson, 1996)+ Prp8 can also crosslink to the invariant GU (Reyes et al+, 1996) and certain alleles of Prp8 can suppress mutations of the U residue at the 59 splice site (Collins & Guthrie, 1999;Siatecka et al+, 1999)+ Our results show, for the first time, that the U5 loop 1 nt U96 to U99 are also in intimate contact with the GU at the 59 splice site+ The U6 snRNA is thought to have a role in catalysis at the 59 splice site, which was recently given further support when yeast U6 was shown to coordinate a metal ion required for catalytic activity of the spliceosome (Yean et al+, 2000)+ The U5 loop 1 is, therefore, well placed for receiving the 59 exon intermediate, resulting from the first catalytic step, for alignment with the 39 exon prior to the second catalytic step+…”
Section: Discussionmentioning
confidence: 53%
“…U6 RNA stereospecifically binds a metal ion at the S p phosphate oxygen 5′ of the highly conserved residue U80 of the ISL (9,12). The S p phosphate oxygen has been shown to be essential for the first step of splicing (7)(8)(9); a sulfur substitution at this position in Saccharomyces cerevisiae U6 halts splicing after the assembly of the spliceosome (9). Splicing activity is rescued with the addition of the thiophilic metal ion cadmium, demonstrating the importance of metal ion coordination at U6 ISL residue U80 for spliceosome function (9).…”
mentioning
confidence: 99%
“…The S p phosphate oxygen has been shown to be essential for the first step of splicing (7)(8)(9); a sulfur substitution at this position in Saccharomyces cerevisiae U6 halts splicing after the assembly of the spliceosome (9). Splicing activity is rescued with the addition of the thiophilic metal ion cadmium, demonstrating the importance of metal ion coordination at U6 ISL residue U80 for spliceosome function (9). Recently, structural studies have shown that protonation of a C67·A79 wobble pair modulates metal ion binding at U80, suggesting a possible method for splicing regulation (12).…”
mentioning
confidence: 99%